Tari Tanun dalam Perspektif Etnokoreologi sebagai Representasi Identitas Budaya Masyarakat Kota Sawahlunto - Dindha Atika Sukma; Yan Stevenson; Hardi Hardi; Syielvi Dwi Febrianti (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to describe and analyze the Tanun Dance from an ethnocoreological perspective as a representation of the cultural identity of the people of Sawahlunto City. The research focuses on the emergence of the Tanun Dance, its presentation form, and the socio-cultural context underlying its existence within the community. This study employed a qualitative method with a dance ethnography approach within the framework of ethnocoreological studies. Data were collected through observation, interviews, documentation, and literature review. The informants consisted of the choreographer of Tanun Dance, the first dancer, and Silungkang songket weavers. Data analysis was conducted through data collection, data reduction, data presentation, and conclusion drawing and verification. The results indicate that the Tanun Dance originated from the weaving activities (batanun) of the Silungkang community, which were later stylized into an artistic performance form. The movements in the Tanun Dance were inspired by weaving activities such as arranging threads, moving the turak, dyeing yarn, and tidying woven fabrics. Performance elements including movements, musical accompaniment, properties, costumes, floor patterns, and presentation structure represent the socio-cultural life of the weaving community. The Tanun Dance functions not only as entertainment, but also as a medium for cultural preservation, cultural education, and a symbol of cultural identity of the Sawahlunto community. Through an ethnocoreological approach, the Tanun Dance is understood as a cultural product reflecting the values of perseverance, patience, skill, and the collective memory of the Silungkang community toward the songket weaving tradition as local cultural heritage.